2010
DOI: 10.1177/0040517510380108
|View full text |Cite
|
Sign up to set email alerts
|

Thermal protective performance of protective clothing used for low radiant heat protection

Abstract: A laboratory simulation was performed to study the thermal protective performance of fabric systems under low level thermal hazards in the range of 6.3—8.3 kW/m2 . Two approaches were used. The first used a method similar to the ASTM F 1939, radiant heat resistance test, while the second used a modification designed to capture the contribution to skin burn injury due to energy stored in the test specimens being released after the direct exposure had ended. Both dry and wet specimens were tested. In order to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(37 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Interestingly, this behavior is observed also when the stored energy effect is considered. Previous studies have shown that the heavier fabric systems and those with air layers, while providing better thermal insulation , also possess superior capacity to store greater amounts of thermal energy, which can be subsequently released to the skin during cooling after exposure to heat . However, it must be noted that this improved thermal insulation works not only during exposure but also during the cooling of the fabric assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this behavior is observed also when the stored energy effect is considered. Previous studies have shown that the heavier fabric systems and those with air layers, while providing better thermal insulation , also possess superior capacity to store greater amounts of thermal energy, which can be subsequently released to the skin during cooling after exposure to heat . However, it must be noted that this improved thermal insulation works not only during exposure but also during the cooling of the fabric assembly.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially useful for the determination of TPE values: the iterative method requires the experimenter to expose the specimen several times to heat, with each trial's exposure time adjusted according to the previous trial's result. This is very time‐consuming, and sometimes only an approximate result can be obtained . The proposed regression method provides a suitable means to determine the TPE values more conveniently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge is also very relevant when developing automotive environments or artificial microclimates for workplaces [4,5]. Several thermal manikins and experimental procedures have been developed to evaluate the performance of different types of products under various conditions [6][7][8][9][10][11]. Zhao et al [6] used a thermal manikin to study the influence of design features of a ventilated clothing on cooling performance, while Elabbassi et al [10] used a similar approach to analyse the efficiency of an electric-heated blanket in preventing hypothermia in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [6] used a thermal manikin to study the influence of design features of a ventilated clothing on cooling performance, while Elabbassi et al [10] used a similar approach to analyse the efficiency of an electric-heated blanket in preventing hypothermia in neonates. The usual procedure consists of setting constant temperature or heat flux on the manikin surface [6,[8][9][10], corresponding to skin values of an human in a state of thermal comfort. Recently, the surface temperature and sweat rates of some thermal manikins have been controlled by mathematical models of human thermoregulation [7,12,13].…”
Section: Introductionmentioning
confidence: 99%